Reduction of Drug Abuse in Adolescents Previously Treated with Stimulants for ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
The effects of early stimulant medication on subsequent risk for cigarette smoking and substance use disorders (SUDs) were evaluated in a 5-year, case-controlled, follow-up study of adolescent girls with ADHD at the Pediatric Psychopharmacology Program, Masachusetts General Hospital, Boston, MA, and Department of Psychiatry, New York State University, Syracuse, NY.